PENGENALAN MATEMATIKA MELALUI METODE HYPNOTEACHING DI PAUD ROSELLA PONTIANAK UTARA - Kurnia, Etika; Fadillah, Fadillah; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract                                                                                                                                          The introduction of mathematics through hypnoteaching methods is required as progress in the learning process. The study collaborated with peers and 4-5 year old A-age children, 9 children. This research is done because the lack of ability of teachers in applying various methods in introducing mathematics to children so that children in PAUD Rosella still not well developed. Teachers are less able to manage learning activities and understand learning in introducing children's mathematics. Research conducted in the first cycle using the method of hypniteaching obtained average results below 50% with good results and in the second cycle is still using the same method of hypnoteaching methods obtained results above 80% with good category. From the activities that have been done then it is suggested that teachers can apply the learning by using hypnoteaching method, so that children do not get bored, so that teachers and children are active in learning activities and always motivate children to the spirit in the learning process. Keywords: Mathematical Introduction, Hypnoteaching Method